Synthesis of Butyl-β-D-Galactoside in the Ternary System: Acetone/1-Butanol/Aqueous Solution - Ahumada, Diego; Arenas, Felipe; Martínez-Gómez, Fabián; Guerrero, Cecilia; Illanes, Andrés; Vera, Carlos (Frontiers in Bioengineering and Biotechnology, 2020)
The enzymatic synthesis of short-tailed alkyl glucosides is generally carried out in an aqueous-organic biphasic reaction medium with a rather low fatty alcohol concentration in the aqueous phase (where the synthesis occurs). Thus, hydrolytic reactions have a significant impact on the synthesis performance. Given this background, the use of acetone as cosolvent was studied for the synthesis of butyl-β-galactoside with Aspergillus oryzae β-galactosidase. The liquid-liquid equilibrium of the reaction mixture components (acetone /1-butanol/ aqueous solution) was determined and the single- and two-phase regions were defined at 30, 40 and 50°C. It was observed that the liquid-liquid equilibrium of the ternary system acetone/1-butanol/water differs significantly from the one obtained using an aqueous solution (50 mM McIlvaine buffer pH 4.5; 5 g·L-1) instead of water. This is mainly because of the salting-out effect of the buffer; nevertheless, the presence of lactose also altered the equilibrium. Having this in mind, the effects of temperature (30 and 50°C) and reaction mixture composition were assessed. Three general conditions were evaluated: single-phase ternary system (30% acetone), two-phase ternary system (10% acetone) and two-phase binary system (0% acetone). Acetone had a deleterious effect on enzyme stability at 50 °C, leading to low reaction yields. However, no enzyme deactivation was detected at 30°C. Moreover, a reaction yield of 0.98 mol·mol-1was attained in the 30/50/20% (w/w) mixture of acetone/1-butanol/aqueous solution. This very high yield can be explained by the huge increase in the concentration of 1-butanol and the reduction of water activity. The synthesis was carried out using also the β-galactosidase immobilized in glyoxal-agarose and amino-glyoxal-agarose, and by aggregation and crosslinking. In the case of agarose-derived catalysts, two average particle diameters were assessed to evaluate the presence of internal mass transfer limitations. Best yield (0.88 mol·mol-1) was obtained with glyoxal-agarose derivatives and the particle size had non-effect on yield. The chemical structure of butyl-β-galactoside was determined by NMR and FT-IR.